2007
DOI: 10.1097/01.blo.0000238785.98606.9d
|View full text |Cite
|
Sign up to set email alerts
|

Early Migration Pattern of the Uncemented CLS Stem in Total Hip Arthroplasties

Abstract: We performed this investigation to determine the possible migration starting immediately after surgery and the effect of different weightbearing regimens on the migration pattern of an uncemented hip stem (CLS). Stem migration was determined with radiostereometry analysis with baseline when the patients still were anesthetized. Subsequent examinations were done up to 1 year. Twenty-nine patients (mean age, 55 years; range, 26-63 years) were randomized to either unrestricted weightbearing combined with intensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
53
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 11 publications
6
53
1
1
Order By: Relevance
“…2). This pattern of early migration has been reported previously with other cementless stems; however, there is limited information in the literature regarding a definitive cause for this early migration [20][21][22]. Impaction of the stem during the early postoperative phase may account for this finding of migration limited to the first six months.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…2). This pattern of early migration has been reported previously with other cementless stems; however, there is limited information in the literature regarding a definitive cause for this early migration [20][21][22]. Impaction of the stem during the early postoperative phase may account for this finding of migration limited to the first six months.…”
Section: Discussionsupporting
confidence: 70%
“…Impaction of the stem during the early postoperative phase may account for this finding of migration limited to the first six months. While our study did not evaluate the pattern of subsidence within the first six postoperative months, a previous study of migration in a cementless stem showed the majority of stem subsidence occurs within the first two months with no major stem migration occurring within the first week of implantation [22].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Even in worst-case scenario, the revision rate was acceptable. It was reassuring to find no evidences of osteolysis or loosening which have been reported in some early-term studies of the CLS prosthesis (Genterpulse, Bern, Switzerland), which has a design similar to that of the COREN prosthesis 30) . The COREN acetabular cup also showed good results.…”
Section: Discussionmentioning
confidence: 80%
“…Continuing rapid early migration is said to be predictive of loosening [22]. However, the absolute early migration is different depending on the stem design [6,22,23,29,[34][35][36][37]. We found that early migration, as measured by EBRA-FCA at 2 years postoperatively, can identify uncemented femoral components at risk for aseptic loosening during early and mid-term followup, but did not predict aseptic loosening in the late second and third decades.…”
Section: Discussionmentioning
confidence: 98%